Worldwide Meniere's disease research: A bibliometric analysis of the published literature between 2002 and 2021 - Zou, Wujun; Li, Qian; Peng, Fei; Huang, Dingqiang (Frontiers in Neurology, 2022)
Background: In recent years, there has been an increasing number of publications on Meniere's disease. However, there are no bibliometric researches on Meniere’s disease. The purpose of this study was to find the focus and trends of Meniere’s disease research through bibliometric approach. Methods: Publications related to Meniere’s disease in the Web of Science Core Collection from 2002 to 2021 were collected. The bibliometric approach was used to estimate the searched data. Research foci of the studies were identified using VOSviewer and CiteSpace software. Results: A total of 1987 articles meet the inclusion criteria and are included in the study. In the past 20 years, the number of Meniere’s disease publications are gradually increasing, especially in the past three years. The country with the largest contribution to Meniere’s disease research is the United States, followed by Europe and Japan. High-frequency keywords included Meniere’s disease, endolymphaic hydrops, vertigo, meniere-disease, inner ear, dizziness, symptoms, hearing, diagnosis, and tentamicin. The analyses of keyword burst direction indicates that evoked myogenic potential, MRI and committee are emerging research hotspots. Conclusion: This study provides an objective, systematic, and comprehensive analysis of the Meniere’s disease-related literature. In addition, current hotspots and future trends in the Meniere’s disease field are identified. This study will help otolaryngologists, neurologists and audiologists to clarify the research direction and potential hotspots of Meniere’s disease, and further help clinicians improve patients’ prognosis.